2b+3=3b-5

Simple and best practice solution for 2b+3=3b-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2b+3=3b-5 equation:


Simplifying
2b + 3 = 3b + -5

Reorder the terms:
3 + 2b = 3b + -5

Reorder the terms:
3 + 2b = -5 + 3b

Solving
3 + 2b = -5 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
3 + 2b + -3b = -5 + 3b + -3b

Combine like terms: 2b + -3b = -1b
3 + -1b = -5 + 3b + -3b

Combine like terms: 3b + -3b = 0
3 + -1b = -5 + 0
3 + -1b = -5

Add '-3' to each side of the equation.
3 + -3 + -1b = -5 + -3

Combine like terms: 3 + -3 = 0
0 + -1b = -5 + -3
-1b = -5 + -3

Combine like terms: -5 + -3 = -8
-1b = -8

Divide each side by '-1'.
b = 8

Simplifying
b = 8

See similar equations:

| b^2+4b+5=0 | | 5+4x=-5+6x | | 3.5+8= | | 7a+2a-6a+3=30 | | 8a-6+16=42 | | 8n+5=6n+7 | | 4a*2a+2=10 | | -21-145= | | 2x+18+4x-24=180 | | 3-4m-5m=14+2m | | 4(a-6)+6=2(a-5) | | 33(6+3)= | | 3(14-2)=36 | | -4(4k-6)=-2(6k+8) | | 5+2(3t-7)=3(2t+5)+24 | | 2x+45=10x-75 | | 16-(2m+8)=3+3m-15 | | -25=-3x-2x | | 1/3(2x-3)=4 | | 1/2/2/3 | | -4(1-8a)=4a+3(1+7a) | | 31/2/2/3 | | -7(5+3p)=7(-p-5) | | 38+(-15)+(-14)= | | -2x+7=6x+15 | | x+1/4=-1/8{8x-2} | | 4(v+6)=30+7v | | 5+3x+1-x=-6+3x+7-2x | | 8y-2=18 | | 17-(4m+6)=5+4m-18 | | -12-2x=8(8-5x) | | 5xy+10=25 |

Equations solver categories